2013
DOI: 10.5598/imafungus.2013.04.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Surveys of soil and water reveal a goldmine of Phytophthora diversity in South African natural ecosystems

Abstract: Phytophthora species are well-known as destructive plant pathogens, especially in natural ecosystems. It is ironic, therefore, how little is known regarding the Phytophthora diversity in South African natural woody ecosystems. In this study, Phytophthora species were isolated using standard baiting techniques from 182 soil and water samples and these were identified based on ITS and coxI sequence data. The 171 resulting Phytophthora isolates resided in 14 taxa including six known species (P. multivora, P. cape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 36 publications
8
61
0
Order By: Relevance
“…Using traditional isolation techniques, Phytophthora assemblages have been characterised in Europe and North America , Argentina (Greslebin et al 2005) and South Africa (Oh et al 2013) with many of the same taxa isolated from trees, soil or water samples. The few metabarcoding studies of Phytophthora communities reveal an ever-increasing diversity.…”
Section: Phytophthora Species Detected Within Australiamentioning
confidence: 99%
“…Using traditional isolation techniques, Phytophthora assemblages have been characterised in Europe and North America , Argentina (Greslebin et al 2005) and South Africa (Oh et al 2013) with many of the same taxa isolated from trees, soil or water samples. The few metabarcoding studies of Phytophthora communities reveal an ever-increasing diversity.…”
Section: Phytophthora Species Detected Within Australiamentioning
confidence: 99%
“…in the case of P. chlamydospora (Brasier et al 2003, Schwingle et al 2007). Phytophthora chlamydospora recently was identified from soil and streams from the Mpumalanga and KwaZuluNatal provinces of South Africa (Oh et al 2013). It is not yet known what plants these species infect in South Africa, but Salix spp.…”
Section: Figmentioning
confidence: 99%
“…A recent investigation, conducted more or less at the same time as the present study, found a great diversity of Phytophthora spp. from soil and water samples from several woody ecosystems of South Africa (Oh et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumption is now being cast in doubt due to the widespread identification of Phytophthora spp. in streams and forests from across the globe (6)(7)(8)(9)(10)(11)(12)(13). Currently, these species are hypothesized to be waterborne opportunistic pathogens, foliar pathogens, and fine-root or canker pathogens (14).…”
mentioning
confidence: 99%